Self-improvement of summability factors of functions satisfying the reverse Hölder inequality in limit cases - Korenovskii, A. A.; Fomichev, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We show that the best summability factors of functions that satisfy the reverse Hölder inequality in limit cases can be obtained from the nonlimit case by passing to the limit.